Analysis of Productive Zakat in Maqosid Ash- Shari'ah Ibnu 'Ashur’s Perspective - Abdul Wasik (ADP Publisher, 2023)
Productive zakat is giving zakat to mustahik that are unsquandered for free but developed as capital to aid their efforts in generating works. Nonetheless, it still presents various problems regarding the type of administration to benefit mustahik zakat, like the concept of Maqosid Asy-Shari'ah Ibnu 'Asyur. The goal of this research is to describe, from the perspective of Maqosid Asy-Shari'ah Ibnu 'Asyur, the concept of productive zakat and how to enhance the community's economy by redirecting productive zakat from a consumptive society to a productive society.This study uses library research that employs the descriptive analysis method, which entails gathering data, compiling or clarifying, and compiling and interpreting it in order to clearly describe the object under study naturally, both from the structure of the sentence, the structure of discourse, and the structure of the semantic. According to the findings of this study, Productive Zakat incorporates Maqid al-shari'ah through three elements: first, by using Al-Maqm. The second is Al-Tamyz Baiyna Al-Waslah Wa Al-Maqud, and the third is Istiqra (induction).